(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: The increasing prevalence of diabetes over the world has become an important public health issue. It is considered as an independent risk factor for cognitive impairment. The cognitive function of patients with type 2 diabetes mellitus is usually not assessed in routine checkup. Objectives: To evaluate the cognitive status and associated factors of type 2 diabetes mellitus patients. Materials and Methods: This cross-sectional study conducted in Combined Military Hospital, Dhaka from July 2014 to June 2015. A total of 191 type 2 diabetes mellitus patients were studied to find out the association between glycemic status and cognitive capacity among the patients. Cognitive capacity was assessed by using MMSE scale. Data were collected by face to face interview with a semi-structured questionnaire and checklist following systematic random sampling technique. Results: Out of 191 patients 85.3% of the patients had uncontrolled DM but 88% of the patients had normal level of cognitive capacity and only 12% having border line cognitive capacity. More male (16.0%) than female (7.1%) patients had border line cognitive capacity. Statistically significant (p<0.05) association was found with age group and glycemic status, aged group has more uncontrolled diabetes mellitus. Majority (39.4%) of elderly patients (61-80 years) had border line cognitive capacity while most (96.4%) of the younger patients (41-50 years) had normal cognitive capacity. Conclusion: In this study type 2 DM patients found with decline in cognitive capacity. So, patients with type 2 DM should be regularly assessed for their cognitive function. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 19-21